2012
DOI: 10.1371/journal.pone.0039882
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Dependence Associated with Increased Utilitarian Moral Judgment: A Case Control Study

Abstract: Recent studies indicate that emotional processes, mediated by the ventromedial prefrontal cortex (VMPC), are of great importance for moral judgment. Neurological patients with VMPC dysfunction have been shown to generate increased utilitarian moral judgments, i.e. are more likely to endorse emotionally aversive actions in order to maximize aggregate welfare, when faced with emotionally salient personal moral dilemmas. Patients with alcohol dependence (AD) also exhibit impairments in functions mediated by the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 36 publications
4
24
2
3
Order By: Relevance
“…As this article was going to press, Duke and Bègue published a study (2015) showing the opposite -that blood alcohol content is positively correlated with increased utilitarianism in responses to trolley problems. This complements existing studies, which have shown that subjects with VMPFC damage due to long-term alcohol abuse tend to be more utilitarian in their judgments (Khemiri et al 2012).…”
Section: Resultssupporting
confidence: 83%
“…As this article was going to press, Duke and Bègue published a study (2015) showing the opposite -that blood alcohol content is positively correlated with increased utilitarianism in responses to trolley problems. This complements existing studies, which have shown that subjects with VMPFC damage due to long-term alcohol abuse tend to be more utilitarian in their judgments (Khemiri et al 2012).…”
Section: Resultssupporting
confidence: 83%
“…Nevertheless, future work should use neuropsychological measures of impulse control or biological markers of affective disturbance such as salivary cortisol (Dallman, 2005). The current demonstration of utilitarian responding in alcohol-dependent individuals is consistent with prior work, including a previous study in a Swedish sample (Khemiri et al, 2012). The utilitarian bias observed in the current sample also appears to be broader than the pattern observed in our prior work in a polysubstance-dependent group (Carmona-Perera et al, 2012a,b), in which the bias emerged only high-conflict personal dilemmas.…”
Section: Discussionsupporting
confidence: 87%
“…Typically, participants are instructed to choose between a utilitarian option (i.e., harming one person to save a greater number of people) and a deontological option (i.e., refusing to harm someone and thus allowing a greater number of people to die). Alcoholdependent individuals have been shown to endorse utilitarian options in response to moral dilemmas (Khemiri et al, 2012). Furthermore, among polysubstance users, severity of alcohol use predicts the degree of utilitarian bias (CarmonaPerera et al, 2012a,b) 2 .…”
mentioning
confidence: 99%
“…Because we show that variations in emotional experience, but not in subjective perceptions of moral content, are associated with utilitarian biases, we reason that the interventions for individuals with moral judgment problems should focus on training and shaping emotional response, rather than working on the “rules” characterizing moral violations. These type of emotional interventions may be useful to restore social decision-making in patients with acquired brain injuries (Koenigs et al, 2007; Moretto et al, 2010), psychopathy (Blair, 2007; Young et al, 2012) or drug addictions (Carmona-Perera et al, 2012; Khemiri et al, 2012). Our results should be also interpreted in the context of its relevant limitations.…”
Section: Discussionmentioning
confidence: 99%